Viola barhalensis (Violaceae), a new species from northeastern Turkey - Knoche, Gerd; Marcussen, Thomas (Phytotaxa, 2016)
A new species, Viola barhalensis Knoche & Marcussen, from northeastern Turkey, is described and illustrated for the first time. It is found at elevations of 1050–1800 m, growing in shady crevices of igneous cliffs within the valley of the Barhal (or Altıparmak) river. It belongs to Viola subsection Viola, and is similar to Viola sandrasea and some other closely related Turkish endemics. Diagnostic morphologic features to enable detailed differention are discussed.